Economic vs. organizational perspective on inter-organizational relations' analysis - are economists on the dead-end track? - Beata Stepien; Monika Sulimowska-Formowicz (Institute of Economic Research (IER), 2015)
Inter-organizational relations (IORs), complex constructs existing on the verge of companies' boundaries, are a popular area of managerial and academic investigation, due to their ability to create sustainable competitive advantage. The aim of the article is to show applicability, insights and limitations of economic perspective in IORs analysis. By reviewing advances of selected economic and organizational theories exploring IORs, we will try to answer the following questions: a) can economic thought add any novelty to IOR analysis in the era of dynamic global shifts in competitive environment?, are economic lenses still useful and applicable here?, b) do organizational sciences' academics take more practical, down to earth approach or have they just moved forward (or blurred the clarity of) their theories by employing advances from social sciences, like sociology and psychology?, c) are these two perspectives contradictory or supplementary? The article is divided into four parts. Firstly, we propose an analytical framework to study inter-organizational relations, secondly we analyze theories focused on IORs as results of rational choices; thirdly we go to theories exploring reasons why IORs are built in a specific way, and then to concepts looking for conditions, methods and key drivers of IORs successful management. In conclusion we give a brief summary of the main findings together with the limitations and open areas of further investigation of inter-organizational relations.
Keywords: D01; D02; D03; D23; D85; L21; L22; 330; inter-organizational relations theory; transaction costs theory; NEI; resource based view; relational view